From blight to benefit: the potential of vacant lot greening to support ecosystem services - Hemsath, Emily Ann (Kansas State University, 2024)
Overgrown vacant lots have become an issue in disinvested neighborhoods with declining populations across the US. However, studies have shown that spontaneous vegetation on vacant lots has the potential to support a high degree of biodiversity and provide significant ecosystem services in urban environments (Kim et al., 2015; McPhearson et al., 2013; Riley et al., 2018). While a city’s ultimate goal for a site is often redevelopment into economically productive uses (Bowman & Pagano, 2004; Németh & Langhorst, 2014), vacant land should not be ignored while waiting for development and should be managed to promote social and ecological goals (Chen & Conroy, 2023; Kim et al., 2018; Rega-Brodsky et al., 2018). Many cities faced with a high number of vacant lots work with community members to green vacant lots (Sadler & Pruett, 2017). However, greening approaches for vacant lots typically seek to create a conventional residential lawn aesthetic, with mown turf and ornamental plantings, significantly reducing the site's biodiversity (Kim et al., 2015; Nassauer et al., 2021). This study aims to address the contradictions between vacant lots’ negative impacts and ecosystem services and suggests converting vacant lots to greenspaces with high biodiversity. Focusing on nine of these highvacancy neighborhoods of Kansas City, Missouri, as a case, this study aims to propose temporary design interventions for vacant lots that would enhance the ecosystem services provided to a community and contribute to an improved quality of life while waiting for redevelopment to occur. This study takes four key steps: a) Use ArcGIS to categorize the vacant lots into a typology based on their redevelopment potential; b) Use aerial imagery to estimate the ecosystem services currently provided by the vacant lots in one focus area, including carbon sequestration, microclimate regulation, stormwater management, and food production; c) Propose greening design interventions for the lots within the selected focus area based on spatial characteristics; and d) Calculate the ecosystem services provided by implementing the proposed design interventions across three alternative scenarios. The findings suggest that the proposed design interventions could improve the provision of the selected ecosystem services across a system of vacant lots. This project offers insights into the environmental value of temporary design interventions for vacant lots through an ecosystem services lens. Additionally, it contributes to the body of literature on landscape performance benefits by demonstrating a method to assess a design proposal’s anticipated ecosystem services through aerial imagery, which can help designers advocate for its implementation.
Keywords: Urban vacancy; Vacant lot greening; Ecosystem services; Landscape performance; Landscape architecture